Multivariable input-output linearization sliding mode control of DFIG based wind energy conversion system - Tohidi, Akbar; Shamsaddinlou, Ali; Sedigh, Ali Khaki (2013 9th Asian Control Conference (ASCC), 2013)
In this paper, obtaining of maximum active and reactive output power for wind turbines equipped with a double fed induction generator using stator-flux-oriented vector control based on novel multivariable input output linearization sliding mode control presented. The main control problem is the estimation of maximum power operating points of wind turbine under stochastic wind velocity profiles and tracking them using conventional offline and innovative adaptive online method. In this control strategy the wind speed and consequent aerodynamics torque is considered as the disturbance. Results under different operating conditions show the superior performance of the proposed online input-output linearization sliding mode technique.